Calcium oxide, potassium phosphite and a Trichoderma enriched compost water suspension protect Capsicum annuum against Phytophthora capsici by priming the immune system. Issue 7 (4th May 2021) - Bellini, Alessio; Pugliese, Massimo; Guarnaccia, Vladimiro; Meloni, Giovanna Roberta; Gullino, Lodovica Maria
Abstract: BACKGROUND: Proper management of Phytophthora capsici in pepper cultivation is extremely important, since Phytophthora blight is the main disease of this crop worldwide. In the past, the main strategy adopted had been the use of fungicides, causing, in some cases, the development of P. capsici resistant strains. In this work three different treatments selected from previous studies (potassium phosphite, calcium oxide and a water suspension from Trichoderma sp. TW2 enriched compost) were tested to prove their ability to activate the systemic acquired resistance (SAR) in pepper against P. capsici ; acibenzolar‐s‐methyl was used as positive control. Two independent growth chamber pot experiments were performed, spatially dividing the site of treatments application (as radical drench) and the site of inoculation (as agar plug on the third leaf). RESULTS: Leaf lesions were measured, showing a significant reduction on all treated plants compared to the untreated control. To further confirm this hypothesis, the expression levels of three SAR key genes ( CaPBR1, CaPO1 and CaDEF1 ) were evaluated though RT‐Real Time PCR at the three end‐point times: T0, T6 and T24. A significant increase of target genes expression at least in one end‐point time in each treated plant was observed. Eventually, statistical overaccumulation of salicylic acid was observed in the upper leaves at the same end‐point times, through HPLC‐MS/MS analysis. CONCLUSION: This work confirmed the hypothesis that the three treatments tested have the ability to prime the plant immune system, leading pepper to an alert status able to confer a better defence against P. capsici . © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Three treatments (Calcium oxide, potassium phosphite and a Trichoderma enriched compost water suspension) were demonstrated to activate the systemic acquired resistance on Capsicum annuum plants against Phytophthora capsici attacks through the study of genes ( CaPBR1, CADEF1 and CAPO1 ) expression and salicylic acid accumulation. ​ © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.